Determinan Impulsive Buying Produk Fashion Menggunakan Pay Later pada Generasi Z di Kota Surabaya - Galuh Ratulangi; Rachma Indrarini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of products, social media marketing, consumer characteristics, and Islamic consumption behavior on impulsive purchases of fashion products using Pay Later. The widespread use of Pay Later and the lack of research linking impulsive purchases with Islamic consumption perspectives form the basis of this study. This study uses a quantitative method with an associative approach. The sample was taken using purposive sampling from Generation Z respondents in Surabaya who had made fashion product transactions using Pay Later. Primary data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results showed that social media marketing and consumer characteristics had a significant positive influence on impulsive buying. Conversely, Islamic consumption behavior has a significant negative effect on impulsive buying, indicating its role as self-control. The product variable was found to have no significant effect on impulsive buying. These findings indicate that consumer characteristics as internal factors are the main drivers, while Islamic consumption behavior as an understanding of Islamic values is the main inhibitor of impulsive buying in this digital era.